ANALISIS PERILAKU PEDAGANG DALAM PERSPEKTIF ETIKA BISNIS ISLAM DI PASAR TRADISIONAL PERENTAK KECAMATAN PANGKALAN JAMBU - Serly Nurvita Dewi; Dedek Kusnadi (ICONS: Islamic Economics Journal, 2026)
This study aims to analyze traders’ behavior in trading activities based on the principles of Islamic business ethics at the Perentak Traditional Market, Pangkalan Jambu District. The research employs a qualitative approach with data collected through interviews, observation, and documentation. The results show that some traders still engage in practices that contradict Islamic business ethics, such as cheating on weights and concealing product quality. However, there are also traders who strive to apply honesty, justice, and responsibility in their trading activities. These findings indicate the need for proper guidance and supervision so that trading behavior in the market aligns with Islamic values, creating a fair, transparent, and blessed trading system for the community.